Willow grouse autosomal heterozygous sites - Kozma, Radoslav; Melsted, Páll; Magnússon, Kristinn P.; Höglund, Jacob (Dryad Digital Repository, 2015)
A vcf file containing the autosomal heterozygous sites of the willow grouse individual. It was generated by the default samtools mpileup and bcftools pipeline. Filtering was performed by vcffilter (from the vcflib suite: https://github.com/ekg/vcflib) to keep only heterozygous sites with read depth between 22 and 136 and mapping quality above 20. Indels were removed by vcftools (v0.1.13), using the '--remove-indels' function.